The Reduction of Infant Mortality in Argentine, Brazil and Uruguay. Among Intentions, Achievements and Challenges - Santillán Pizarro, María Marta (2011)
The importance of infant mortality reduction is internationally recognized in different Human Rights treaties, such as the Convention on the Rights of the Child (CRC). In different Conferences and Summits, these treaties have been reinforced by the inclusion of quantifiable goals in their action plans, which have been adopted by Argentine, Brazil, and Uruguay. Twenty years has passed since the CRC was ratified by these countries. Then, there is a need to assess whether the reduction of infant mortality has been sufficient to attain the goals proposed in those action plans. In this paper, we are interested in the assessment of progress made towards the intended goals and acknowledge unfulfilled commitments to reach them. Based on information published by the National Bureaus of Statistics and the Latin American & Caribbean Demographic Centre (ECLAC - Population Division), we conclude that Argentine, Brazil, and Uruguay have obtained notable achievements in the reduction of child mortality. They reduced infant mortality by one-third between 1990 and 2000 as part of their commitment to the CRC. Nevertheless, despite the continued decrease in infant mortality in subsequent years, the attained outcomes will not be sufficient to reach the proposed goals during 2010 or 2015. Similar situation can be observed when gaps among different social sectors are analyzed. The situation, in this case, is even worse because gaps show unacceptable levels. For this reason, these countries need to increase their efforts to comply with their commitments toward children's rights.